Edukasi dan Penerapan Teknologi Sederhana Infused Water Halal Berbasis Buah dan Sayur untuk Mendukung Hidrasi dan Asupan Antioksidan pada Siswa MA Asshodiqiyah - Kusumawati, Dwi Endah; Lestari, Asih Puji; Suharno, Davia Maulidda; Virdiyanti, Shenia (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Students' health and physical fitness serve as essential foundations for achieving optimal learning outcomes. Nevertheless, many adolescents, particularly those enrolled in Islamic senior high schools (Madrasah Aliyah), have not yet established healthy hydration habits or sufficient intake of natural antioxidants. Inadequate fluid consumption and exposure to free radicals may adversely affect concentration, immune function, and long-term health status. This community service initiative aimed to enhance students' knowledge and skills regarding the importance of proper hydration and the role of antioxidants, as well as to promote healthy lifestyle practices through the preparation of infused water. The program was conducted in December 2025 and involved 21 eleventh-grade students at MA Asshodiqiyah. The methods employed included interactive educational sessions and hands-on practice in preparing infused water. Program effectiveness was evaluated using a pre-test and post-test design with multiple-choice assessment instruments. The findings revealed an 80% increase in the average knowledge scores following the intervention, and all participants (100%) were able to independently prepare infused water. This initiative not only improved students' cognitive understanding but also developed practical skills that may contribute to sustainable behavioral changes toward healthy hydration habits and natural antioxidant consumption both at school and at home.